Analisis Determinan Komitmen, Kompensasi dan Kepemimpinan Transformasional Terhadap Kinerja Karyawan (Studi Kasus di PTPN IV) - Rafidah RAfidah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2018)
This paper aims to analyze the determinant of organizational commitment, compensation and transformational leadership in PTPN IV Jambi. This research uses primary sources by distributing questionaire to its employees,The sample used in this research were employees of PTPN IV – Jambi. The sampling technique was conducted using Random Sampling. quantitavie approach with regression analisys is used to describe the determinant of each variables. The result show that thitung for organizational commitment is 2,814 with significant value 0,006, the for transformtional leadership Thitung is 2,831 with significant value 0,006, and for thitung for compensation is 2,737 with significant value 0,000 smaller than 0,05. its mean all avariables are significant and positively have effect to employe performance in PTPN IV Jambi.